A green route to a novel hyperbranched electrolyte interlayer for nonfullerene polymer solar cells with over 11% efficiency. Issue 5 (3rd January 2018) - Zhou, Dan; Xiong, Sixing; Chen, Lie; Cheng, Xiaofang; Xu, Haitao; Zhou, Yinhua; Liu, Feng; Chen, Yiwang
Abstract : APNSO3 Na organic interfacial layer can induce the active layer to form a bi-continuous nano-micro phase separation face-on orientation. Abstract : A novel environmentally-friendly hyperbranched electrolytePNSO3 Na organic interfacial layer has been synthesized; this can tune the interfacial energy alignment and induce the upper active layer to form a bi-continuous nano-micro phase separation face-on orientation. Based on a PBDB-T:ITIC active layer, the device with a ZnO/PNSO3 Na ETL exhibits a high efficiency of 11.2%.